MENGHITUNG KEBUTUHAN APAR DAN IDENTIFIKASI RESIKO PADA PEMBANGUNAN RUANG BIMA DI PROYEK RSUD DHARMA HUSADA SURABAYA - Santoso, Rani Rachmad; Tyasa, Rizal Bayu; Amarulloh, Aldy Bagus; Putra, Letfrizal Rana; Adigunadarma, Adigunadarma; Rahmadiansyah, Dhio (LPPM Universitas Bina Bangsa, 2024)
The use of light fire extinguishers (APAR) is very important in preventing and handling fires. APAR is a tool designed to extinguish fires at an early stage, so as to prevent fires from becoming larger and more destructive. This research aims to identify the need for APARs in various types of buildings, including residential, office and industrial, as well as to develop guidelines for effective APAR placement and maintenance. The research results show that strategic placement of APARs, adequate training for residents or employees, and routine maintenance are the keys to successful use of APARs. In addition, the type and number of fire extinguishers required vary depending on the size and function of the building. It is hoped that the guidelines developed in this research can help building owners comply with fire safety standards and reduce the risk of loss due to fire